2022
DOI: 10.20885/jeki.vol8.iss2.art4
|View full text |Cite
|
Sign up to set email alerts
|

Spin-off and efficiency in Islamic banks: DEA approach

Abstract: Purpose – This study aims to analyze the efficiency level of Islamic banks from spin-off and non-spinoff results and the impact of the separation policy and other factors that affect the efficiency level of Islamic banks.Methodology – This study uses a quantitative approach through data envelopment analysis to measure the efficiency level of Islamic banks and the difference-in-difference approach to examine the impact of separation and other factors that affect the efficiency level of Islamic banks. Data is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In the aspect of efficiency, based on the ability to generate income from assets (TATR), it is revealed that BNIS is increasingly efficient [22]. This is confirmed by the results of an increasingly efficient DEA analysis [23,24], although some studies reveal that BRIS is more inefficient than before the spin-off [18,25,26]. Similar conditions were also found in the profitability ratios (NPM and ROA) [18,20,27], asset growth, third party funds, financing [19], market share [22], financing productivity [23], and productivity of social funds management [28].…”
Section: Bank Bni Syariahmentioning
confidence: 85%
“…In the aspect of efficiency, based on the ability to generate income from assets (TATR), it is revealed that BNIS is increasingly efficient [22]. This is confirmed by the results of an increasingly efficient DEA analysis [23,24], although some studies reveal that BRIS is more inefficient than before the spin-off [18,25,26]. Similar conditions were also found in the profitability ratios (NPM and ROA) [18,20,27], asset growth, third party funds, financing [19], market share [22], financing productivity [23], and productivity of social funds management [28].…”
Section: Bank Bni Syariahmentioning
confidence: 85%
“…The profitability and efficiency of Islamic banks have been found to decrease after they go through spin-off, as noted in various studies by Poerwokoesoemo (2016) and Hosen & Rahmawati (2016). Spin-off banks exhibit lower levels of efficiency compared to non-spinoff banks (Al Arif & Nabilah, 2022). Small-sized banks, especially regional banks, are particularly vulnerable to the negative impacts of spin-off policy, as stated by Haribowo (2017).…”
Section: Literature Reviewmentioning
confidence: 90%
“…In general, the findings from these studies showed that Islamic bank spin-offs impacted banking performance in Indonesia, both in new Islamic banks from spin-off policy (Kuncoro & Yulianto, 2018;Nasuha, 2012) and in abandoned conventional banks themselves (Poerwokoesoemo, 2016). Specifically for Islamic banks, the impacts included an increase in third-party funds or deposits (Al Arif, 2014Arif, , 2018bNasuha, 2012), increasing profitability (Hamid, 2015;Ramdani, 2015), and increasing market structure and power (Al Arif, 2018b;Rayyani et al, 2022), but decrease in efficiency (Al Arif, 2015a;Hadziq et al, 2022;Nabilah & Al Arif, 2022;Rusydiana et al, 2019). As for financing, some studies found that spin-offs impacted the financing provided (Nasuha, 2012).…”
Section: Islamic Bank Spin-off Study On Sinta Indexed Journalsmentioning
confidence: 99%
“…Regardless of whether it is significant or not, all existing findings showed that spin-offs reduced the efficiency of Islamic banks (Al Arif, 2015a;Al Arif et al, 2019;Hadziq et al, 2022;Nabilah & Al Arif, 2022;Rusydiana et al, 2019;Trinugroho et al, 2021). However, in terms of assets, the spin-off had no impact on Islamic bank assets (Al .…”
Section: Spin-off and Performance/efficiency Of Islamic Banksmentioning
confidence: 99%